Effects of flaxseed supplementation on lipid metabolism, oxidative balance and genetic damage in goats - Cecchini, Maria Eugenia (2018)
Epidemiological evidence indicates that flaxseed reduces oxidative stress and cholesterol levels in blood. In this study we evaluated the lipid profile, oxidation of plasma lipids and genetic damage in goats fed on a diet supplemented with flaxseed. Thirteen adult male goats were split in two experimental groups; one of them was fed on a conventional diet of alfalfa and ground corn and the other group was fed on the same diet supplemented with 5% of flaxseed. Blood samples were obtained every 7 days to quantify the Thiobarbituric Acid-Reactive Substances (TBARs), total cholesterol, HDL, LDL and triacylglycerols. Additionally, 3 blood samples and 3 oral mucosa samples were taken to each animal every 15 days to perform comet assay and micronucleus test. Flaxseed supplementation produces a remarkable antioxidant effect in plasma in a three months period that could explain the antigenotoxic effect determined through both micronucleus test and comet assay. In addition, we also found a reduction of LDL/HDL ratio and cholesterol levels in animals supplemented with flaxseed.